Strategies for Strengthening Students' Religious Character through Habituation, Role Modeling, and School Culture: A Case Study at SDN 1 Aikmual, Praya Central Lombok, Indonesia - Raden Sumiadi; Baiq Dewi Muhimmah; Adi Purmanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to examine the strategies for strengthening students' religious character through habituation, role modeling, and school culture at SDN 1 Aikmual, Praya, Central Lombok. Religious character is one of the fundamental values that should be instilled from the elementary school level as the foundation for developing students' morality, ethics, and behavior in their daily lives. This study employed a qualitative approach using a descriptive research design. Data were collected through observations, interviews, and document analysis involving the school principal, teachers, and students. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that the strategies for strengthening students' religious character at SDN 1 Aikmual are implemented through various religious habituation activities integrated into the school's culture. These activities include regular Imtaq (Faith and Piety) programs, the collective recitation of Surah Yasin every Friday, religious lectures, and the memorization of short chapters (surahs) of the Qur'an. In addition, the school organizes an extracurricular Taman Pendidikan Al-Qur'an (TPQ, Qur'anic Learning Center) outside regular Islamic Religious Education classes to enhance students' Qur'anic reading skills and understanding of the Qur'an. During the month of Ramadan, the school implements peer-assisted Qur'anic memorization and recitation activities in which students actively listen to and evaluate one another's memorization and recitation. These activities foster discipline, responsibility, and enthusiasm for learning Islamic teachings. The role-modeling strategy is reflected in teachers' consistent demonstration of religious values in their daily behavior, while the school culture is developed by creating an environment that continuously supports the practice and internalization of religious values. The findings further indicate that the integration of habituation, role modeling, and school culture effectively strengthens students' religious character, as reflected in their improved discipline in performing religious practices, enhanced ability to read and memorize the Qur'an, greater politeness and respect toward others, and stronger awareness of applying religious values in their daily lives. Therefore, these integrated strategies represent an effective model for strengthening religious character in elementary school settings.